Analysis of Motorcycle Parking Charges in the Klaten City Shopping Area - Ristuningsih, Septiyanti; Hartarto, Romi Bhakti (Journal of Economics Research and Social Sciences, 2021)
The implementation of regional autonomy adheres to the principle that financial sources originating from Regional Original Income (PAD) are more critical than sources outside PAD. Therefore, adequate financial sources are needed to finance the implementation of regional autonomy, one of which is through regional levies. One of the sources of revenue from sizeable regional user fees is parking fees. This sector is one of the essential sources of revenue because it always develops and develops an area (city). If it is appropriately managed, it can support PAD. This study aims to determine the number of potential parking fees in the shopping area of Klaten City and find strategies to optimize the potential for parking fees through surveys, observations, mathematical calculations, and comparative techniques to obtain an overview of the potential and conditions of the parking location. The results obtained include: 1) The potential for parking fees is currently Rp. 2,090,880,000.00 2) The efforts of local governments in increasing parking fees are not optimal 3) Strategies that can be used to increase parking fees can be done by establishing new regulations so that new potential the resulting amount will be IDR 2,471,040,000.00. Based on these findings, this research is expected to be a reference for the Klaten City government in optimizing the potential for parking fees; Besides, it is hoped that this research can enrich previous scientific findings related to parking fees.